Evaluation of Anxiety Levels in Patients Undergoing Intravitreal Injections and Associated Risk Factors Related to the Disease - Juan-Carlos Herranz-Heras; Almudena de-Pablo-Cabrera; Beatriz Alonso-Martín; Beatriz de-Lucas-Viejo; Marta de-Castro-Liébana; Enrique Mencía-Gutiérrez; Manuel-Jesús Ferro-Osuna; Carmen Romero; Javier Sambricio (Journal of Ophthalmology)
Purpose. To analyze patients’ anxiety levels using the Visual Analog Scale for Anxiety (VASA), in regard to intravitreal injection treatment and to determine possible associated risk factors related to the disease and treatment characteristics. Methods. Cross-sectional observational study with consecutive sampling of patients who were going to receive an intravitreal injection. Subjects completed the VASA prior to the procedure, and afterwards, their data were collected from the electronic medical history. Analysis was performed through a linear regression model. Results. Fifty-five men and forty-seven women were enrolled. The mean age was 73.9 ± 12.4 years (mean ± standard deviation (SD)), and the mean ± SD of previous injections was 12.8 ± 12. The most frequent pathologies found were age-related macular degeneration with 46.1% and diabetic macular edema with 36.3%. The median of anxiety levels measured in millimeters (mm) was 16 (interquartile range: 0–48). In univariate models, women presented a mean of 10.8 mm of anxiety more than men (p=0.03). The adjusted multivariate analysis demonstrated that younger patients declared higher anxiety levels (p=0.036). No significant association was found between the best corrected visual acuity (BCVA) on the day of the injection, the change in BCVA since the beginning of the treatment or the number of injections received, and the registered anxiety levels. Conclusions. Sex and age may have an influence on anxiety levels. BCVA and the number ofinjections received did not seem to have an influence on our patients anxiety levels.